2017
DOI: 10.1002/asi.23919
|View full text |Cite
|
Sign up to set email alerts
|

Data set mentions and citations: A content analysis of full‐text publications

Abstract: This study provides evidence of data set mentions and citations in multiple disciplines based on a content analysis of 600 publications in PLoS One. We find that data set mentions and citations varied greatly among disciplines in terms of how data sets were collected, referenced, and curated. While a majority of articles provided free access to data, formal ways of data attribution such as DOIs and data citations were used in a limited number of articles. In addition, data reuse took place in less than 30% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 52 publications
(76 reference statements)
1
47
1
Order By: Relevance
“…Mooney reported that 29% of the sampled publications provided formal citations to datasets in reference lists (Mooney, ). Yet, other studies suggested that a vast majority of the publications provided data citations or mentions in the methods sections (He & Nahar, ; Zhao et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Mooney reported that 29% of the sampled publications provided formal citations to datasets in reference lists (Mooney, ). Yet, other studies suggested that a vast majority of the publications provided data citations or mentions in the methods sections (He & Nahar, ; Zhao et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies demonstrated that researchers use a wide variety of ways to refer to datasets (Callaghan, ; Henderson & Kotz, ; Major, ; Mooney, ; Pepe, Goodman, Muench, Crosas, & Erdmann, ; Zhao et al, ). Belter () supported this by noting that 377 variant formats of citing the same data were found.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations